2017
DOI: 10.1186/s40168-017-0290-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-resolved metaproteomic characterization of preterm infant gut microbiota development reveals species-specific metabolic shifts and variabilities during early life

Abstract: BackgroundEstablishment of the human gut microbiota begins at birth. This early-life microbiota development can impact host physiology during infancy and even across an entire life span. However, the functional stability and population structure of the gut microbiota during initial colonization remain poorly understood. Metaproteomics is an emerging technology for the large-scale characterization of metabolic functions in complex microbial communities (gut microbiota).ResultsWe applied a metagenome-informed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 51 publications
5
57
1
Order By: Relevance
“…Metaproteomics sequencing was conducted on 0.3 g of stool as previously described (Xiong et al 2017). Each sample was suspended in 10 mL cold phosphate buffered saline.…”
Section: Metaproteomics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Metaproteomics sequencing was conducted on 0.3 g of stool as previously described (Xiong et al 2017). Each sample was suspended in 10 mL cold phosphate buffered saline.…”
Section: Metaproteomics Analysismentioning
confidence: 99%
“…However, it is still likely that microbial communities play an important role, with the context-dependent metabolism of specific strains potentially critical to infant health and disease. Recent studies have applied proteomics and metabolomics to premature infant gut microbiomes to measure functional profiles in healthy premature infants and those that went on to develop NEC (Xiong et al 2017;Stewart et al 2016). These studies reported temporal variation in the infant proteome and identified metabolites associated with NEC.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still likely that microbial communities play an important role, with the context-dependent metabolism of specific strains potentially critical to infant health and disease. Recent studies have applied proteomics and metabolomics to premature infant gut microbiomes to measure functional profiles in healthy premature infants and in those that went on to develop NEC ( 18 , 19 ). Those studies reported temporal variation in the infant proteome and identified metabolites associated with NEC.…”
Section: Introductionmentioning
confidence: 99%
“…In a routine (meta)proteomics data analysis [12][13][14][15], to reliably quantify proteins, it is necessary to select the most representative peptides and usually semi-tryptic peptides are not considered, because the expended search space will increase database search time and detection of semi-tryptic peptides was less consistent than that of fully tryptic peptides. In general, semi-tryptic peptides are mainly derived from endogenous proteolysis while the impacts of other factors such as in-source fragmentation and sample degradation are negligible [16,17].…”
Section: Introductionmentioning
confidence: 99%